Area optimization of two-stage amplifier using modified particle swarm optimization algorithm - Ratan S.; Mondal D.; Anima R.; Kumar C.; Kumar A.; Kar R. (My University, 2025)
Modern era cannot be consider without an electronics circuits. If Signal strength at the receiving antenna is very weak then there must be required a device that increase the strength of the received signal (power), known as Amplifier. Output of an amplifier is always stronger than its input. So amplifiers are the simplest yet one of the most important parts of electronic circuits. This is why the designing of amplifiers is crucial in analog circuit designing. This paper investigated to minimize the area of a two stage amplifier using modified particle swarm optimization (MPSO) method considering other constraints. The total transistor area obtain using MPSO in this paper is 2.61×10-10 m2 and it is the best of my knowledge, also the power dissipation is much lesser, 1492 μW. Obtained values are verified by the CADENCE simulator and validated. The results proved that the use of modified particle swarm optimization made it possible to achieve better results. © 2016 IEEE.